2004
DOI: 10.1046/j.1540-8167.2004.04326.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Action of Atrial Dilation and Sodium Channel Blockade on Conduction in Rabbit Atria

Abstract: In dilated atria, blockade of the rapid sodium channels caused a higher degree of local conduction delay and intra-atrial conduction block than in nondilated atria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 31 publications
4
27
0
Order By: Relevance
“…The explanation could be that the basic conductance is for Na + when SACs are activated [21,32], and that a relatively less negative resting membrane potential [13] leads to markedly larger effects of sodium channels blockade and post-repolarization refractoriness. Thus, our data suggest that the effect of sodium channels blockade is strongly enhanced upon acute atrial stretch, confirming a recent experimental report [17].…”
Section: Flecainide Groupsupporting
confidence: 93%
See 2 more Smart Citations
“…The explanation could be that the basic conductance is for Na + when SACs are activated [21,32], and that a relatively less negative resting membrane potential [13] leads to markedly larger effects of sodium channels blockade and post-repolarization refractoriness. Thus, our data suggest that the effect of sodium channels blockade is strongly enhanced upon acute atrial stretch, confirming a recent experimental report [17].…”
Section: Flecainide Groupsupporting
confidence: 93%
“…Also, Zarse et al [16] investigated the effects of verapamil, glibenclamide and cariporide, and concluded that calcium overload plays a crucial role in short-term electrophysiological changes caused by atrial dilatation, as opposed to atrial ischemia or acidosis which have no significant impact. Finally, Eijsbouts et al [17] recently showed that the effects of flecainide on atrial refractoriness were enhanced by acute atrial stretch. With the same model of acute stretch-related AF, we perfused BRL-32872, dofetilide and flecainide after 30 min of sustained AF.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the RA, they were predominantly orientated parallel to the large pectinate muscles. Also, in other studies, 7,22,23 lines of block were found along the long axis of the crista terminalis and large pectinate muscles. In the posterior LA wave boundaries were predominantly oriented in a craniocaudal direction.…”
Section: 'Cracks In the Atrial Wall'mentioning
confidence: 58%
“…10,11 Local conduction velocity was calculated as the mean of two conduction vectors in a 2.5-mm ϫ 2.5-mm area. Slow conduction was defined as local conduction velocities between 10 and 20 cm/s.…”
Section: Regional Conduction: Conduction Slowing and Conduction Blockmentioning
confidence: 99%